A mica/nepheline glass-ceramic prepared by melting and powder metallurgy at low temperatures. (June 2017) - wei, Wei; Yong, Liu; Tan, Yanni; Grover, Liam; Guo, Yu; Bowei, Liu
Graphical abstract: Highlights: Mica glass ceramics were prepared at low temperatures by melting and powder metallurgy. The relative sintered density of mica glass ceramics at 850 °C can be 90%. The microstructures of sintered glass ceramics are well crystallized, with mica and nepheline as main phases. The transverse rupture strength and the hardness of mica glass ceramics can be 97 MPa and 6 GPa, respectively. Abstract: Mica glass-ceramics usually have high melting temperatures. In this work, mica glass-ceramics were prepared by the combination of melting and powder metallurgy at low temperatures. Firstly, a SiO2 -CaO-B2 O3 -MgO-Na2 O-ZnO glass powder with a melting temperature as low as 1000 °C was prepared. Subsequently, the glass powder mixed with different contents of fluorphlogopite was remelted at 1300 °C to synthesize the ultimate glass frit. After disintegration, the mica glass-ceramic powder can be sintered at low temperatures of 800–950 °C, and a relative density as high as 90% can be obtained. The phase constitutions and microstructures of the bulk glass-ceramics were characterized by X-ray diffraction and scanning electron microscopy. The results illustrated that the glass-ceramics were mainly made up of flake-like fluormica and columnar nepheline, accompanied by augite, forsterite and some other minor phases. The transverse rupture strength and the hardness of mica glass-ceramics were both low at 800 °C for the high porosity, and decreased with the increase of mica phase at 850 °C. Nevertheless, the highest strength of the glass-ceramic with 30% mica reached 97.42 ± 10.2 MPa, which can be potentially applied for engineering applications.